Religious co-existence in Malappuram - Muhammad, Muneer Kuttiyani; Ushama, Thameem (IIUM Press, International Islamic University Malaysia, 2017)
Hindu-Muslim relation in Malappuram district of Kerala state in India is noteworthy in terms of its peaceful co-existence since the early Muslim presence in the region. However, there are some attempts to polarize people of both communities, like what colonizers did during colonial invasion. The present study determines the status of religious co-existence prevailing in the current social realm of Malappuram in relation to its historical contributions towards Hindu-Muslim peaceful co-existence. The study also seeks critical analysis of the denunciations put against the district and its people, which threatened the idea of peaceful co-existence and its practicability. The study examines the history, status and features of religious co-existence in the district. The perception of Hindus on the majority Muslims has also been highlighted in the study. The methodology of research is qualitative through library study and examination of relevant information based on books, articles, websites, newspapers, reports of various agencies including interviews of selected personalities. This study highlights the need for a peaceful inter-religious ambience in a society where different people of different faiths live together. The sustenance of the peaceful co-existence between the Muslims and Hindus can be maintained by reiterating the glorious history of the region which has been heavily emphasized in this study.